EKSEKUSI RIIL SENGKETA TANAH ANTARA PT. JONDUL JAYA SAKTI CABANG PEKANBARU DENGAN PIHAK TAHREL DI PENGADILAN NEGERI PEKANBARU - Desy Aulia Ulfa Siregar; Mardalena Hanifah; Rahmad Hendra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
In carrying out a decision (execution), in essence, the losing party oftendoes not want to carry out the decision voluntarily, so that the implementation ofthe judge's decision is carried out by coercion (real execution) by the executingparty with the help of public forces such as the police and even the military. Realexecutions carried out by courts often encounter resistance from executed partieswho do not accept the judge's decision. So many factors can hinder the execution.The land dispute case between the Tahrel Party and PT. Jondul Jaya SaktiPekanbaru Branch has passed all stages of the trial starting from the FirstSession, Appeal, Cassation, even to the extraordinary judicial review. The Court'sdecision stated that the land was the property of Tahrel, but the PekanbaruDistrict Court did not carry out the execution of the land on the grounds thatthere was a lawsuit from a third party.The type of legal research is sociological, which in this research is carriedout by going directly to the field to collect primary data through interviews withthe parties involved in this case, namely the lawyers of PT. Jondul Jaya SaktiPekanbaru Branch, Tahrel, Registrar of the Pekanbaru District Court and Bailiffof the Pekanbaru District Court. This research uses a descriptive method. Thenature of this research is descriptive.The results of this study are the inhibiting factors for the real execution ofland disputes between PT. Jondul Jaya Sakti Pekanbaru Branch with Tahrel atthe Pekanbaru District Court were the losing parties (PT. Jondul Jaya SaktiPekanbaru Branch) resisted with a lawsuit from a third party. The executioncould not be carried out because it was still waiting for a lawsuit decision from athird party. Efforts made in overcoming the inhibiting factors for the execution ofreal land disputes between PT. Jondul Jaya Sakti Pekanbaru Branch with theTahrel Party at the Pekanbaru District Court, namely the winning party (Tahrel)submitted an application for forced implementation of the Judge's decisionthrough the competent District Court. Tahrel submitted a request for re-executionto the Head of the Pekanbaru District Court to carry out the execution for theumpteenth time, namely the first on 18 July 2019, the second 28 July 2019 and thethird 5 August 2019.Keywords: Real execution, land dispute, Pekanbaru District Court